1998
DOI: 10.3109/03639049809085648
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Delivery of Isosorbide 5-Mononitrate from a New Membrane Reservoir and Matrix-Type Patches

Abstract: Isosorbide 5-mononitrate (5-ISMN) has a direct relaxing effect on vascular smooth muscle. In the present study we developed matrix and reservoir-type transdermal patches of 5-ISMN. We investigated the usefulness of a new film-forming material isolated from the roots of Salacia macrosperma to serve as rate-controlling membrane for the reservoir-type patches. Matrix-type patches were formulated using polyvinyl chloride. Permeation studies through rat skin were conducted on both types of patches using Teflon cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…13,14) Different types of terpenes have been shown to be effective penetration enhancers for both hydrophilic 15,16) and lipophilic drugs.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…13,14) Different types of terpenes have been shown to be effective penetration enhancers for both hydrophilic 15,16) and lipophilic drugs.…”
Section: )mentioning
confidence: 99%
“…11,12) It has been suggested that terpenes increase the penetration of drugs through the skin by disrupting the intercellular packaging of stratum corneum lipids and by increasing drug diffusivity. 13,14) Different types of terpenes have been shown to be effective penetration enhancers for both hydrophilic 15,16) and lipophilic drugs. 17,18) Nerolidol is an amphiphilic and highly lipophilic sesquiterpene (log P 5.36± 0.38).…”
Section: )mentioning
confidence: 99%
“…Transdermal therapeutic systems (TTSs) are a typical example of DDSs. Therapeutic medicines in TTSs that have already been marketed include tulobuterol for the treatment of bronchial asthma, 1) clonidine for hypertension, 2) nitroglycerin and isosorbide dinitrate for angina pectoris, 3,4) and rivastigmine for Alzheimer's disease. 5) However, the enhancement of skin permeation is sometimes required for drugs.…”
mentioning
confidence: 99%
“…2) nitroglycerin and isosorbide dinitrate for angina pectoris, 3,4) and rivastigmine for Alzheimer's disease. 5) However, the enhancement of skin permeation is sometimes required for drugs.…”
mentioning
confidence: 99%